Daily Behavior of Binturong (Arctictis binturong) in Ex-situ Conservation Taman Margasatwa Ragunan - Widya Anggraini; Mia Azizah; I.G.A Manik Widhyastini (JURNAL SAINS NATURAL, 2023)
Binturong (Arctictis binturong) is a mammal in the family of Viverridae, which includes animals such as civets. Binturong is a species with VU (Vulnerable) status, which means that it faces the risk of extinction in the wild in the future based on the International Union for Conservation of Nature and Natural Resources (IUCN) Red List and has Appendix III based on the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES). This research aimed to determine the behavior at Taman Margasatwa Ragunan (Ragunan Wildlife Park) from July to September 2022. Taman Margasatwa Ragunan is an ex-situ conservation for flora and fauna, which is also helpful as a place for research, education, and recreation. This research determined the behavior, frequency, and duration of binturong’s daily activities at Taman Margasatwa Ragunan (Ragunan Wildlife Park). This study used a scan sampling method, and the objects were three individual binturongs, namely male Sumatran binturong (Martin), male Kalimantan binturong (Amoy), and female Kalimantan binturong (Gaza). The results obtained showed that the highest activity was found in resting behavior (6444 minutes; 82,64%) and the lowest was in agonistic behavior (3 minutes; 0,03%) carried out by Martin, then the highest activity was in resting behavior (6607 minutes; 84,75%) and the lowest was the behavior of defecation (5 minutes; 0,06%) carried out by Amoy, then the highest activity was in resting behavior (6833 minutes; 87,61%) and the lowest was the behavior of defecation (1 minute; 0,01%) carried out by Gaza.